(untitled) (Journal of Asian Development Studies, 2024)
The present study compared teachers’ performance evaluation practices of public and private sector schools at the secondary level. The study’s objectives were to examine the performance evaluation practices at public and private sector secondary schools and to compare the performance evaluation practices between public and private sector schools at the secondary level. The study’s target population was public and private sector secondary school head teachers and teachers. One hundred schools were selected through a random sampling technique. Data were collected from 100 head teachers and 329 teachers to examine and compare the performance evaluation practices at secondary schools. Based on the literature review, an instrument was developed. The reliability coefficient of the instrument was found to be 0.898. Data were collected personally and analyzed by using SPSS. Headteachers’ and teachers’ opinions were solicited on a five-point Likert scale. The Chi-square test was applied to compare the responses of head teachers and teachers from public and private secondary schools. It was found that in both public and private schools, the most commonly used practices for the performance evaluation of teachers were "how they maintain their teacher’s diary, their punctuality, their contribution towards organizing the sports and co-curricular activities, organization of games, by taking feedback from colleagues, by visiting their classrooms and from the result of the students in exams.